NEW WAY TO DETERMINE THE TYPE OF ADAPTATION STRATEGY IN EXPERIMENT - S. N. Bocharov; M. L. Lebed; M. G. Kirpichenko; V. V. Gumanenko (Acta Biomedica Scientifica, 2012)
Aim: to base and to test new more precise way of determination of the type of adaptation strategy and. intensity of corresponding metabolic shifts in experiment. Methods: the model of orthopedic trauma of two extremities with stabilization of fragments with external fixation devices was rendered in experimental group of 22 chinchilla rabbits. We defined oxygen consumption, carbonic acid excretion and rectal temperature initially and also on the 1st, 3rd and 7th day after the operation. Results. Addition of data of research of oxygen consumption (key criterion of the type of adaptation strategy) with the results of determination of carbonic acid excretion and rectal temperature, correct choice of initial condition of laboratory animal that will be compared and also quantitative characteristics of intensity of metabolic shifts allowed to increase exactness of diagnostics of type of adaptation strategy of laboratory animals in unfavorable conditions.